Effects on gastric mucosa induced by dental bleaching - an experimental study with 6% hydrogen peroxide in rats - Anabela Baptista PAULA; Maria Isabel DIAS; Manuel Marques FERREIRA; Teresa CARRILHO; Carlos Miguel MARTO; João CASALTA; António Silvério CABRITA; Eunice CARRILHO (University of São Paulo, 2015)
The value of aesthetic dentistry has precipitated several developments in the investigation of dental materials related to this field. The free marketing of these products is a problem and it is subject to various interpretations regarding its legality. There are several techniques for tooth whitening, the most used one being the external bleaching. It is the later version of such technique that poses the greatest danger of ingesting the product. The present study analysed the systemic effect of these products when they are swallowed.Objective This experimental study aimed to observe the effects of a tooth whitening product, whose active agent is 6% hydrogen peroxide, on the gastric mucosa of healthy and non-tumour gastric pathology animals.Material and Methods Fifty Wistar-Han rats were used and then distributed into 5 groups, one for control and four test groups in which the bleaching product was administered in animals with and without non-tumour gastric pathology (induced by the administration of 1 sample of 50% ethanol and 5% of drinking water during 6 days) at different times of study by gavage. There was a decrease in body weight in animals of groups handled during the study period, which was most pronounced in IV and VA groups. Changes in spleen weight relative to body weight revealed no statistically significant changes. An analysis of the frequency was performed on the results of macroscopic observation of the gastric mucosa.Results The gastric mucosa revealed lesions in all manipulated groups, being more frequent in groups III and IV. It appears that there is a synergism when using hydrogen peroxide and 50% ethanol in the same group.Conclusion Therefore, it seems that there are some signs of toxicity 3 to 4 days after administration of 6% hydrogen peroxide. The prescription of these therapies must be controlled by the clinician and the risks must be minimized.